Reliability evaluation of reinforced concrete columns designed by Eurocode for wind-dominated combination considering random loads eccentricity. Issue 1 (January 2020) - Jiang, Youbao; Peng, Suixiang; Beer, Michael; Wang, Lei; Zhang, Jianren
With the capacity models in the 2004 edition of the European Committee for Standardization's Standard Design of Concrete Structures, a more realistic limit state function is obtained for reinforced concrete columns with random loads eccentricity. Using this function, the applicability of the code-based design factors is discussed. Taking the wind-dominated combination as an example, the probabilistic distribution of loads eccentricity and the statistics of column resistance are analyzed for representative cases. The analysis indicates that the possible loads eccentricity is scattered over a large range, and the probabilistic model of column resistance varies from case to case, which is largely different from the resistance model assumed in previous reliability calibration. With Monte Carlo simulation, the column reliability and the contributions of both tension failure and compression failure to the total failure probability are calculated and obtained for different cases. The results show that the fixed loads eccentricity criterion underestimates differences in the reliability of columns for different loads eccentricity cases and overestimates the column reliability in some tension failure cases. Furthermore, it is found that the tension failure mode contributes most to the total failure probability for not only some columns designed to fail in tension failure but also for some columns designed to fail in compression failure. To attain a robust design, a group of optimum wind load factors varying with cases is recommended. The new calibration results prove that the recommended wind local factors can achieve a better goal.